2019
DOI: 10.1080/15384101.2019.1642068
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Loss of exosomal MALAT1 from ox-LDL-treated vascular endothelial cells induces maturation of dendritic cells in atherosclerosis development

Abstract: Objectives: Maturation of dendritic cells (DCs) contributes to atherosclerosis (AS) development. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a long non-coding RNA (lncRNA) that is involved in tumorigenesis. This study was designed to explore the role of exosomes from oxidized low-density lipoprotein (oxLDL)-treated vascular endothelial cells (VECs) in regulating DCs maturation in AS, and to elucidate whether MALAT1 was involved in this process. Methods: Human umbilical VECs (HUVECs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…ECs compared with the normal ECs (Li et al 2019). This difference suggests that the role of MALAT1 in AS remains unclear and deserves a multi-center investigation.…”
Section: However LI and Colleagues Found Lower Expression Of Malat1 mentioning
confidence: 82%
“…ECs compared with the normal ECs (Li et al 2019). This difference suggests that the role of MALAT1 in AS remains unclear and deserves a multi-center investigation.…”
Section: However LI and Colleagues Found Lower Expression Of Malat1 mentioning
confidence: 82%
“…We hypothesize that the high expression of MALAT1 in serum and exosomes originates from the cells surrounding pathological tissues and thus cause a decline in plaques. However, Li and colleagues found lower expression of MALAT1 in exosomes of ox-LDL-treated ECs compared with the normal ECs ( Li et al, 2019 ). This difference suggests that the role of MALAT1 in AS remains unclear and deserves a multi-center investigation.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Recent studies have shown that autophagy plays a vital role in the behavior of vascular cells, such as ECs and VSMCs. Li et al found that exosomal miR-221/222 derived from human aortic smooth muscle cells (HAOSMCs) inhibits autophagy in HUVECs by partly regulating the PTEN/Akt signaling pathway when HUVECs and HAOSMCs are co-cultured ( Li et al, 2016 ).…”
Section: Exosomal Non-coding Rnas In the Pathophysiology Of Coronary mentioning
confidence: 99%